Eolian deposits associated with the alluvial plain of the Desaguadero River, Mendoza province, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
On the right bank of the Desaguadero river and the distal piedmont of the Andean Precordillera, there are important aeolian accumulations that have received little attention to date (Figs. 1,4). Thesedeposits, recognized in different previous regional studies, are grouped within a complex unit called “Médanos y Guadales” (Polanski, 1963; González Díaz y Fauqué, 1993; Rodríguez y Barton, 1993; Costa et al., 2001).The main objective of this work was to analyze the geomorphological characteristics of the area in detail, considering sedimentological, stratigraphic and chronological features of the units, in order to make a contribution into the knowledge to dateabout the regional geological evolution.The geomorphological analysis was based on satellite image interpretation by means of a Geo- graphic Information System (GIS). Fieldwork was conducted to verify the characteristics of mapped units and get further details on their morphological and morphometric traits. A general sampling of the units was made taking superficial sediment through small holes up to 50 cm - 1 m deep. Sediment sam- ples were processed at the laboratory for particle size characterization by sieving and Bouyoucostechni- ques, and mineralogical composition by binocular magnifying glass (10X) and microscope. Conventional radiocarbon dates were obtained based on residues gastropod shells, calcium carbonate and carbon.The geomorphological analysis allowed to establish that aeolian deposit consists of three major landforms as lunette dunes, linear or longitudinal dunes and sandy mantles (Fig. 6). The lunette du- nes are landforms of particular importance in the region because of the information they provide as a paleoenvironmental and paleoclimatic indicator. The size of this type of dune, with asymmetrical cross sections and face steeper windward, is influenced by the size of the beach or ephemeral lake which is associated to it (Thomas, 1989; Holliday, 1997; Lancaster, 2005). Pye and Tsoar (2009) note that as parabolic dunes, the arcuate plan form of the lunettes indicates wind direction, and the sedimentation on the surface of the dune is generally improved by the presence of vegetation. They further note that, unlike the parabolic dunes, lunettes are rarely transgressive causing fix dunes.In this study we differentiated lunette dunes associated with temporary ponds (DL1) and lunette dunes associated to deflationary depressions and temporary ponding (DL2). The former develop large parallel cords to morphology of coastal temporary ponds and can reach several kilometers long and up to 14 m high. They are distributed in at least five altimetric levels which are linked to different stages in an overall shrinkage of river flows during the Holocene (Figs. 7,8). The DL2 correspond to lunette dunes of smaller dimensions, with less than 3 m heights and lengths between 300 and 700 m. They also shows a characteristic plan morphology with a straight central section and ends in “horns” pointing eastward.The longitudinal sand dunes occur commonly grouped into dune fields, with variable wave lengthsbetween 100 and 200 m, 2 to 4 m height and 100 to 400 m long, and sandy mantles are characterized by their large surfaces and thin thicknesses, generally less than 50 cm.The superficial texture of aeolian deposits shows a difference between the lunette dunes DL1, with predominantly sandy texture, regarding DL2, with sandy loam textures, which can be associated with higher energy, fluvial-lacustrine depositional envi- ronment of the source areas. Longitudinal dunes have a higher content of medium sized sand than lunettes dunes, possibly associated with higher wind energy. The sandy mantles have higher contents of silt than longitudinal dunes and lunette dunes, due to its reworked by alluvial action.The mineralogical composition indicates a ge- neral predominance of quartz and subordinate plagioclase, with abundant undifferentiated lithic fragments. The gypsum and fragments of shells are abundant in the lunettes dunes, with presence of shattered glass that usually does not exceed 5% of the total sample. These data are consistent with the mineralogy of the fluvial deposit of the Desaguadero riverbed, from where it is estimated to come most of the grains. The spatial arrangement of the lunette dunes allows inferring winds from East and Southeast.The lunette dunes comprise the oldest preserved aeolian deposits in the study area and rest on the Arco del Desaguadero Formation, whose period of deposition comprising the upper Pleistocene- Holocene. Based on the dates obtained in the AltoGrande lunette dune (1210 ± 50 C14 yr BP and 690± 90 C14 yr BP) its formation is assigned to upper Holocene, during the period known as the Optimum Medieval Warm when climatic conditions have allowed further development of the vegetation cover and the fixing of temporary ponds marginal cords.The geomorphological and stratigraphic feature of the longitudinal sanddunes allow to infer sub- sequent development of lunette dunes during the Little Ice Age by means of winds coming from East and Southeast. The development of sandy mantle is considered partially contemporaneous with the development of longitudinal dunes with posterior remobilization associated with sporadic surface runoff.Currently the aeolian morphogenesis is partially restricted due to a higher density of vegetation cover, which is linked to the general increase inprecipitation, at least during the last 60 years.
Keywords: unette Dunes, Linear Dunes, Aeolian- Fluvial Interaction, UpperHolocene, Desaguadero River, Mendoza.